Rekonstruksi Hukum Perikatan Islam pada Komoditas Unggulan Kepulauan Sula di Era Digital - AKBAR TAKIM Liem Akbar (Sekolah Tinggi Agama Islam Babussalam Sula, 2026)
This empirical-legal qualitative study examines the reconstruction of Islamic covenant law in digital transactions of featured commodities across the Sula Islands. The background of this study is the shift of conventional trade toward Facebook and WhatsApp platforms in Sanana, which has created friction between the flexibility of cyber-market technology and the classical fiqh doctrine of ittihad al-majlis. This study aims to answer two questions, namely the extent to which Islamic covenant law is effectively applied in such transactions, and how an ideal legal reconstruction formula can be developed. Data were collected through social media observation and in-depth interviews with local MSME actors and legal practitioners, then analyzed inductively through the lens of sociology of law and Maqashid Shariah. The results show that the application of Islamic covenant law is sociologically effective, as the principle of mutual consent (an-taradhin) is fulfilled through trust-based social capital, yet remains legally weak due to the absence of written contracts and down-payment systems, leaving business actors vulnerable to gharar and unilateral breach of contract. As a reconstruction formula, this study proposes an integrative three-pillar model: legitimizing digital footprints as a modern form of Al-Kitabah, reorienting the contractual session into a virtual majlis, and perfecting qabdh through the strengthened role of local couriers as wakil al-mushtari. This study contributes a more operational legal model compared to previous studies, which generally addressed these three aspects separately.